Optimising publicity: towards a theoretical model - Ndojisile Theys; André van Deventer; Dalmé Mulder (Acta Academica, 2009)
Generating a continuous presence in the media and targeting mass audiences with predetermined marketing communication messages in the process does not have to be synonymous with large budget allocations and the advertising dimension of integrated marketing communication (IMC) only. Publicity can establish such a media presence with mass audiences without any cost to the organisation. However, this technique of IMC is often neglected and underutilised. A literature review as a non-empirical and qualitative research design was undertaken to develop a theoretical model that can assist marketing communication practitioners in optimising the use of publicity in the marketing communication mix.